A possibilidade de concessão de Habeas Corpus para transgressões disciplinares militares - Medeiros Filho, Walmir Pereira (2007)
The Habeas corpus originated in the Roman Right like injunction of homine exhibendo. It survived at the times and gained strength, or was reborn, in 1215, in England with the promulgation of the Charter of King John to the Barons. Originaly, had like doing legal nature so that the person was returned to the freedom and it links and they were taken the case to a judge so that he judged them. With the Habeas corpus Act of 1679, the writ of habeas corpus started to have guarantees so that it was carried out. In the Brazilian Right, the historical landmark of the Habeas corpus was the Decree of 23 of May of 1821, which added the institute officially to our ordenament, without, nevertheless to quote the name, which only took place with the advent of the Criminal Code of 1830.The habeas corpus evolved in Brazil of 1821 up to our days, with, with three clear periods of retreat: from 1930 to 1934, from 1937 to 1946 and from 1964 to 1985. The current Constitution guarantees the concession of the writ in all his plenitude, when the cases of punishment are excepted, in what the Judicial thing must not judge the merit of the punishment, but only the legality of the act as for his form, and in this sense it has been being most of the decisions in which habeas corpus was petitioned against disciplinal punishment when had been how illegal.